Menguatkan Ketahanan dan Kohesi Sosial dalam Upaya Mencegah Intoleransi dan Radikalisme di Masyarakat melalui Program Desa Damai Wahid Foundation di Malang Raya - Faizin, Nurul; Mustofa, Bisri; Rosyidah, Inayatur (LPPM STAI Ihyaul Ulum Gresik, 2021)
This study examines the initiatives of peaceful villages (Desa Damai) in fostering social resilience and cohesion to prevent intolerance and radicalism within communities through the Desa Damai program of the Wahid Foundation in Malang Raya. Employing a qualitative descriptive methodology, this research adopts a grounded theory approach, focusing on Candirenggo Village (Malang Regency) and Sidomulyo Village (Batu City) as the objects of study. Primary data were collected through interviews, observations, and specifically designed instruments, while secondary data were gathered from documentation and official archives, including relevant literature and supporting materials. The study involves 5–10 informants from each research location, with the exact number determined based on data needs and sufficiency to achieve data saturation. Grounded theory is utilized for data analysis, and the validity of the findings is ensured through data and source triangulation.The research findings reveal that a peaceful village is characterized by inclusivity and harmony across diverse groups, races, and religions. These villages foster tolerance, reject violence, and maintain ideological and economic resilience. One of the primary objectives of establishing peaceful villages is to support community livelihoods, achieved in part through the formation of small women's business groups. Furthermore, the initiative promotes peaceful coexistence and counters radical influences, emphasizing the empowerment of women as a strategy to enhance tolerance and prevent radicalism and terrorism.